Use of psychotropic substances among elite athletes - a narrative review - Exner J.; Bitar, R.; Berg, X.; Pichler, E.-M.; Herdener, M.; Seifritz, E.; Claussen, M. C. (Swiss Medical Weekly, 2021)
BACKGROUND AND AIMS: Elite athletes may use psychotropic substances for recreational reasons, (perceived) performance enhancement or self-medication. Causes can overlap. For athletes, substance use may be associated with various medical and social risks. Psychoactive substances include alcohol and nicotine, illicit and various prescription drugs, which all have a potential for abuse and dependence. This paper reviews the existing literature on the use of psychoactive substances and associated substance use disorders among elite athletes in terms of prevalence, patterns of use, as well as underlying causes and risk factors.